Rhythm, Music, and the Brain: Scientific Foundations and Clinical Applications - Thaut, Michael -1952 (New York Routledge, 2005)
With the advent of modern cognitive neuroscience and new tools of studying the human brain live, music as a highly complex, temporally ordered and rule-based sensory language quickly became a fascinating topic of study. The question of how music moves us, stimulates our thoughts, feelings, and kinesthetic sense, and how it can reach the human experience in profound ways is now measured with the advent of modern cognitive neuroscience. The goal of Rhythm, Music and the Brain is an attempt to bring the knowledge of the arts and the sciences and review our current state of study about the brain and music, specifically rhythm. The author provides a thorough examination of the current state of research, including the biomedical applications of neurological music therapy in sensorimotor speech and cognitive rehabilitation. This book will be of interest for the lay and professional reader in the sciences and arts as well as the professionals in the fields of neuroscientific research, medicine, and rehabilitation.
The structure of rhythm : the essence of time in music -- Aesthetics and psychobiology -- The neural dynamics of rhythm -- Biomedical research in music -- Rhythm-driven optimization of motor control -- Music in therapy and medicine : from social science to neuroscience -- Neurologic music therapy in sensorimotor rehabilitation -- Neurologic music therapy in speech and language rehabilitation -- Neurologic music therapy in cognitive rehabilitation.
Keywords: Science; Music philosophy and esthetics; Music therapy; Rhythm